Effects of H+ and OH− on H2O as probed by the 1-propanol probing methodology: differential thermodynamic approach. Issue 40 (4th October 2017) - Koga, Yoshikata; Miki, Kumiko; Nishikawa, Keiko
Abstract : Two-dimensional characterization map of H + and OH −, together with other ions. Abstract : We applied what we call the "1-propanol (1P) probing methodology" on the effects of H + and OH − on liquid H2 O. We found that H + is an amphiphile with a modest hydrophobic and an equally modest hydrophilic contribution. Its hydration number is 2 ± 1, suggesting that the equilibrium hydration structure is like the Zundel type (H5 O2 + ). OH −, on the other hand, has a large hydration shell with 12 ± 3 H2 O molecules and acts as a hydrophobe-like hydration center. In other words, it forms a hydration shell around itself, but as the probing 1P increases and the available H2 O decreases, it exerts its influence over a longer range and reduces the hydrogen-bond probability of bulk H2 O away from hydration shells, just as a hydrophobe does to bulk H2 O.